A generic assessment of waste disposal at Douala City practice, prinicipals and uncertainties - Atangana, Abdon (University of the Free State, 2013)
One reason why groundwater, so often constitutes the main source of drinking water in many cities and towns around the world, is because it is frequently present in sufficient quantities at the point of demand. However, this seemingly advantage may sometimes be its greatest disadvantage, especially in situations where the groundwater occurs at shallow depths and the area overlying the aquifer is populated densely. This problem is particularly relevant in the present technological age with its vast quantities of waste that is often disposed in an uncontrolled manner. Such a situation occurs at Douala the economic capital of Cameroon in central Africa. The city not only host more than 80% of industries in the country, but also has the largest urban population of approximately 3 000 000 with a population density of approximately 350 persons per square kilometre, which continue to increase at a rate of approximately 120 000 migrants per year from the rural areas, while the groundwater level is very shallow and may sometimes rise above the soil surface, especially during floods, which occur not too infrequently. Although the pollution problem is not restricted to groundwater as such, it is aggravated here, because of the ancient belief that wastes are safely disposed of, if buried below the earth’s surface. It took disasters like Love Canal and the Price Landfill to discover the detrimental effects that this practice may have on the population living on or near polluted aquifers. Extreme care therefore should be exercised to prevent the pollution of any aquifer that may pose problems to living organisms or to try and restore a polluted aquifer threatening the natural environment. Groundwater pollution should therefore receive urgent attention when discovered. This thesis describes an attempt to develop a set of guidelines for the restoration of the groundwater resources at Douala, based on the relatively new technique of permeable reactive barriers for groundwater remediation—a technique that is also increasingly applied in the restoration of the Superfund sites in the United States of America. Modern attempts to clean up contaminated aquifers, relies heavily on the use of suitable computational numerical models. Such models have in the past always been based on the classical hydrodynamic dispersion equation. However, an analysis of the equation in this thesis has shown that the equation cannot account for the long‐tail contamination plumes characteristic of fractured rock aquifers. Fortunately, it is not too difficult to develop a more suitable equation. For, as shown in the thesis, all that one has to do is to replace the ordinary derivatives in the classical equation with fractional derivatives. Mechanistic modeling of physical systems is often complicated by the presence of uncertainties, which was in the past usually neglected in the models used in the restoration of aquifers.While these uncertainties have regularly been neglected in the past, it is nowadays imperative that any groundwater model be accompanied by estimates of uncertainties associated with the model. Although a large number of approaches are available for this purpose, they often require exorbitant computing resources. The present investigation was consequently limited to the application of the Latin Hypercube Sampling method applied to an analytical solution of the hydrodynamic dispersion equation. It has been known for years that the hydrodynamic dispersion equation discussed in Chapter 5, is not able to account for the long‐tail plumes often observed in studies of contaminated fractured‐rock aquifers. An approach frequently used to account for this is to replace the ordinary spatial and temporal derivatives in the hydrodynamic equation with fractional derivatives—a procedure confirmed in this thesis.

Een van die redes waarom grondwater gereeld die primêre bron van drinkwater in baie stede en dorpe in die wêreld is, is omdat dit teenwoordig is in voldoende hoeveelhede wanneer dit benodig word. Ongelukkig is hierdie voordeel dikwels ’n groot nadeel, veral in digsbevolkte gebiede met vlak grondwatervlakke. Hierdie probleem kom veral voor in digsbevolkte gebiede wat voortdurend groot hoeveelhede afval genereer en dit op ŉ ongekontroleerde wyse wegdoen. Dit is onder andere die geval in Douala, die ekonomiese hoofstad van die staat Kameroen in sentraal Afrika. Die stad huisves meer as 80% van die industrie in die land en het ook die grootste stedelike bevolking van ongeveer 3 000 000 met ŉ digtheid van plus minus 350 persone per km2 wat elke jaar met sowat 120 000 vanaf die landelike gebiede toeneem. Die grondwatervlak is baie vlak en dagsoom dikwels tydens vloede watgereeld voorkom. Alhoewel die besoedelingsprobleem nie beperk is tot grondwater as sulks nie, word dit hier vererger deur die historiese geloof dat afval veilig gestort word as dit in die grond begrawe word. onder die. Dit het rampe soos die Love Canal en die Price stortingsterrein gekos om mense te besef dat hierdie praktyk uiters negatiewe impakte op die bevolking in die onmiddellike omgewing van besoedelde akwifere mag hê. Uiterste voorsorg moet dus getref word om te verhoed dat akwifere besoedel word. Hierdie proefskrif beskryf ŉ poging om ŉ stel riglyne daar te stel vir die herstel van die besoedelde grondwaterbronne van te Douala, wat gebaseer word op die redelike nuwe tegniek van deurlaatbare reagerende versperrings—ŉ tegniek wat ook in die skoonmaak van die sogenaamde “Superfund” terreine in die VSA toegepas word. Hedendaagse pogings om besoedelde akwifere skoon te maak, steun geweldig op die gebruik van geskikte rekenaar gebaseerde numeriese modelle. Hierdie modelle is tot nog toe gewoonlik op die klassieke hidrodinamiese dispersiewe vergelyking gebaseer. Die ondersoek wat vir hierdie proefskrif onderneem is, ondersteun egter die hedendaagse siening dat hierdie vergelyking nie besoedelingspluime met lang agterstukke—’n karakteristieke eienskap van besoedelingspluime in gekraakte akwifere—kan beskryf nie. Soos getoon in hierdie proefskrif, kan die probleem geredelik oorkom word deur klassieke afgeleides wat in die hidrodinamiese dispersievergelyking voorkom met breukafgeleides te vervang. Meganistiese modellering van fisiese sisteme is altyd onderhewig aan onsekerhede wat in die verlede gewoonlik in modelle van sulke geïgnoreer is wat gebruik is in die restourasie van akwifere. Hierdie onsekerhede is in die verlede gewoonlik geïgnoreer. Deesdae is dit egter noodsaaklik dat modelle skattings van dié onsekerhede moet bevat. Alhoewel daar ŉ groot verskeidenheid van metodes bestaan wat vir hierdie doel gebruik kan word, vereis dit dikwels buitensporige hulpbronne. Die huidige ondersoek is daarom beperk tot die aanwending van Latynse hiperkubus monsters, wat toegepas is op ŉ analitiese oplossing van die hidrodinamiese dispersiewe vergelyking wat getoon het dat dit uiters geskik vir die doel is.
Thesis (Ph.D. (Institute for Groundwater Studies))--University of the Free State, 2013
Keywords: Groundwater -- Cameroon; Waste disposal in the ground -- Cameroon; Drinking water -- Contamination -- Cameroon; Analytical and numerical models; Mathematical; Groundwater remediation; Fractional derivatives; Uncertainty and sensitivity analyses; Groundwater flow equation; Hydrodynamic dispersion equation; Douala City; Groundwater pollution